De Novo Assembly and Characterization of the Transcriptome of the Parasitic Weed Dodder Identifies Genes Associated with Plant Parasitism. Issue 3 (7th January 2014) - Ranjan, Aashish; Ichihashi, Yasunori; Farhi, Moran; Zumstein, Kristina; Townsley, Brad; David-Schwartz, Rakefet; Sinha, Neelima R.
Abstract : Transcriptional dynamics during parasitism in the parasitic weed Cuscuta pentagona reveals increased expression of genes encoding transporters and stimulus response regulators, and a decrease in the expression of genes encoding photosynthetic proteins . Abstract: Parasitic flowering plants are one of the most destructive agricultural pests and have major impact on crop yields throughout the world. Being dependent on finding a host plant for growth, parasitic plants penetrate their host using specialized organs called haustoria. Haustoria establish vascular connections with the host, which enable the parasite to steal nutrients and water. The underlying molecular and developmental basis of parasitism by plants is largely unknown. In order to investigate the process of parasitism, RNAs from different stages (i.e. seed, seedling, vegetative strand, prehaustoria, haustoria, and flower) were used to de novo assemble and annotate the transcriptome of the obligate plant stem parasite dodder ( Cuscuta pentagona ). The assembled transcriptome was used to dissect transcriptional dynamics during dodder development and parasitism and identified key gene categories involved in the process of plant parasitism. Host plant infection is accompanied by increased expression of parasite genes underlying transport and transporter categories, response to stress and stimuli, as well as genes encoding enzymes involved in cell wall modifications. By contrast, expression of photosynthetic genes is decreased in the dodder infective stages compared with normal stem. In addition, genes relating to biosynthesis, transport, and response of phytohormones, such as auxin, gibberellins, and strigolactone, were differentially expressed in the dodder infective stages compared with stems and seedlings. This analysis sheds light on the transcriptional changes that accompany plant parasitism and will aid in identifying potential gene targets for use in controlling the infestation of crops by parasitic weeds.